2018
DOI: 10.1002/jcph.1366
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Exposure‐Response Analyses for CPX‐351 in Patients With Hematologic Malignancies

Abstract: CPX‐351, a dual‐drug liposomal encapsulation of cytarabine and daunorubicin at a synergistic ratio, is approved in the United States for adults with newly diagnosed therapy‐related acute myeloid leukemia or acute myeloid leukemia with myelodysplasia‐related changes. Population pharmacokinetics analyses were performed using nonlinear mixed‐effect modeling on pooled data from 3 clinical studies, and the impact of CPX‐351 exposures on efficacy and safety was assessed. The pharmacokinetics of cytarabine and daunor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To address this issue, nanocarrier‐based systems for codelivery of multiple drugs have increasingly been empoldered to offer a spatio‐temporal unification of separate pharmacokinetics of different drug payloads, which are evidenced to be more effective in preclinical and clinical studies . For instance, Vyxeos, a liposomal preparation coloaded with cytarabine and daunorubicin (5:1 molar ratio), has been approved by the U.S. Food and Drug Administration for acute myeloid leukemia treatment . Vyxeos can maintain a constant 5:1 drug ratio in the plasma of patients for up to 24 h after intravenous administration, which shows significantly enhanced anticancer efficacy with prolonged survival period compared with the conventional cocktail of cytarabine and daunorubicin (7:3 molar ratio) …”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, nanocarrier‐based systems for codelivery of multiple drugs have increasingly been empoldered to offer a spatio‐temporal unification of separate pharmacokinetics of different drug payloads, which are evidenced to be more effective in preclinical and clinical studies . For instance, Vyxeos, a liposomal preparation coloaded with cytarabine and daunorubicin (5:1 molar ratio), has been approved by the U.S. Food and Drug Administration for acute myeloid leukemia treatment . Vyxeos can maintain a constant 5:1 drug ratio in the plasma of patients for up to 24 h after intravenous administration, which shows significantly enhanced anticancer efficacy with prolonged survival period compared with the conventional cocktail of cytarabine and daunorubicin (7:3 molar ratio) …”
Section: Introductionmentioning
confidence: 99%
“…These results are supported by a previous population PK analysis comparing exposures of CPX-351 in patients with hematologic malignancies with mild and moderate renal impairment vs. normal renal function. Wang et al reported a similar mean AUC tau between patients with normal renal function and mild/moderate renal impairment for daunorubicin and cytarabine in an analysis of data collected from three clinical studies of patients with advanced hematologic malignancies, AML or acute lymphocytic leukemia, and newly diagnosed high-risk/secondary AML [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…Previously, the results of a population pharmacokinetic (PK) analysis indicated that no dose adjustments of CPX-351 were needed for patients with hematologic malignancies and mild/moderate renal impairment [ 18 ]. However, the effect of severe renal impairment on the PK and side effect profile of CPX-351 has not been established.…”
Section: Introductionmentioning
confidence: 99%